Effects of Functional Acupuncture on Upper Limb Spasticity After Ischemic Stroke: A Protocol for a Randomized Controlled Parallel Clinical Trial - Mei, Jinjin; Xue, Yang; Li, Jingwen; Zhang, Lihong; Zhang, Jianyun; Wang, Yiying; Su, Kaiqi; Gao, Jing; Guo, Jian; Li, Ruiqing (Frontiers in Neurology, 2022)
Background: Upper limb spasticity is a common complication after stroke, which seriously affects the quality of life and rehabilitation of patients. There are different treatment methods for post- stroke spasticity. Our group found that the spasticity of the upper limbs after stroke can be effectively improved by adopting the Functional Acupuncture (FA), alleviate motor function and improve the quality of life. Then this topic is mainly to study the clinical efficacy of FA in the treatment of upper limb spasticity after ischemic stroke. Method: This is a parallel design and randomized controlled trial. We will select 84 patients who meet the predefined criteria and randomize them into two groups, experimental group, control group. The experimental group receive Functional Acupuncture (FA) and routine rehabilitation treatment. The control group receive Traditional Acupuncture (TA) and routine rehabilitation treatment. All patients will receive 20 courses of treatment for 4 weeks, and the modified Ashworth score (MAS), clinical neurological deficit score (CSS), Fugl-Meyer upper limb function assessment (FMA-UE) and the Modified Barthel Index Score (MBI) will be evaluated before and after treatment. Discussion: This trail is mainly to study the clinical efficacy of FA in the treatment of upper limb spasticity after ischemic stroke. It will not only provide a new idea for the clinical treatment of upper limb post-stroke spasticity, but also will provide effective experimental support and theoretical basis for clinic.